Avaliação do modelo formativo do PRONATEC: aspectos da inserção educacional e produtiva dos egressos dos cursos de qualificação profissional do IFCE - Castro, Daniel Ferreira de (2017)
This work is based on the Research Line “Design of Social Public Policies” under the Graduate Program on Evaluation of Public Policies at the Federal University of Ceará (UFC). It is focused on the problem of finding out the socio-educational impacts of Pronatec (National Program for the Access to Technical Education and Employment) on the lives of youngsters and workers who have completed Initial and Continuing Education (FIC) Programs. The main objective of this scientific research was to evaluate the formative conception of Pronatec, by analyzing the social and professional insertion process of the beneficiary public. The specific goals of this research were: to analyze and debate the ideological and political dimensions that substantiated the implementation of BolsaFormação/Pronatec (Empowerment Scholarship/Pronatec); understand the socio-cultural and structural factors that made Empowerment Scholarship/Pronatec graduates seek vocational training; debate the quality of the Empowerment Scholarship/Pronatec programs based on the evaluation of graduates; and get to know the social repercussions of the Empowerment Scholarship/Pronatec offer on the lives of its beneficiaries. Methodologically, the phenomenon was evaluated both qualitatively and quantitatively, through documentary analysis of the institutional records of the Program at the IFCE, interviews with local and national managers as well as the application of a questionnaire among the graduates from FIC programs. The theoretical reference was based on studies by authors such as Alves (2011); Antunes (2002); Frigotto (2001, 2011, 2015); Frigotto, Ciavatta and Ramos (2005); Manfredi (1998); Melo and Moraes (2006); Oliveira (2011); Sousa (2011), among others. Based on those theoretical principles, this research recognizes that the Education and Work relationship has become a social process of legitimizing changes in the labor market, and that vocational education in Brazil has been considered as the driving force of economic development over the last years. It was found out that Pronatec, with the predominant offer of FIC programs, was aimed at meeting the supposed demand for vocational training for the labor market, as well as for the development of a private educational market, through the massive use of public funds to finance vocational training actions. This formative model continued the historical trend of training for simple work in Brazil, dissociating its actions from an effective proposal to increase the schooling level of the beneficiary subjects. Pronatec was a little effective concerning the graduates’ employability issue, and its vocational training policy was disconnected from the labor and income policies. On the other hand, although graduates, managers, and education theorists seriously criticize the quality of such formative model, the program has improved its performance in relation to the expansion of educational access